Aerodynamic study of a 'humpy' propeller. (1st January 2012) - Marinus, B.G.; Bosschaerts, W.; Roger, M.
A detailed aerodynamic study of a 'humpy' high-speed propeller is presented. This propeller is the result of a bi-disciplinary optimisation procedure and features blade segments of wider chord bordered by narrow segments. The aerodynamic consequences of these regions are investigated and correlated to the aeroacoustic properties by comparison to an equivalent blade without hump.